PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB PADA MATERI PEMOGRAMAN WEB DI KOTA BATAM - Efendi, Aldino; Saragih, Saut Pintubipar (Computer Science and Industrial Engineering, 2021)
Now a days, there are many ways to learn by using the internet. One of those is “E-Learning” where student and teacher use the platform to do a learning and teaching. It has been benefit the education world. A better online platform is needed to give student more efficiency for learning and teacher for teaching online by using video for the learning materials. In this study, “SDLC Waterfall” method will be used where assessing needs, system design, coding making, program testing, implementation and maintenance stages will be included. As a result of the study, the information system has more efficient to get information and time saving.